2003
DOI: 10.1093/jac/dkg478
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of combinations of antipseudomonal agents against seven strains of multidrug-resistant Pseudomonas aeruginosa

Abstract: The three-drug combination of ceftazidime, aztreonam and amikacin may be effective against P. aeruginosa resistant to all commonly used antipseudomonal drugs, and deserves further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…Okazaki et al have investigated effectiveness of phosphomycin combination against MDRP by the efficacy time index [10]. Oie et al have reported that the combination of AZT and amikacin was the most effective, inhibiting proliferation in MDRP [11]. Our data also suggested synergistic effects of GM, especially in combination with AZT and PIPC.…”
Section: Methodssupporting
confidence: 62%
“…Okazaki et al have investigated effectiveness of phosphomycin combination against MDRP by the efficacy time index [10]. Oie et al have reported that the combination of AZT and amikacin was the most effective, inhibiting proliferation in MDRP [11]. Our data also suggested synergistic effects of GM, especially in combination with AZT and PIPC.…”
Section: Methodssupporting
confidence: 62%
“…A number of in vitro studies have demonstrated a synergistic activity against MDRP strains when colistin is combined with rifampicin [14,15] or with amikacin [16,17]. However, no clinical studies carried out to date have demonstrated the superiority of combining colistin with other antimicrobials over monotherapy [18].…”
Section: Discussionmentioning
confidence: 99%
“…This study was presented at the 47th Interscience Conference on Antimicrobial Agents and Chemotherapy (ICAAC), Mc Cormick Place Lakeside Center, Chicago, Illinois, that was held on September [17][18][19][20] 2007.…”
mentioning
confidence: 99%
“…Several authors prefer combination regimens for the treatment of serious S. maltophilia infection, particularly in individuals immunocompromised because of the bacteriostatic mode of action of most agents and the potential for the development of resistance during monotherapy [56]. Strategies for salvage therapy of MDR P. aeruginosa infection include combining agents that individually have limited activity against the organism [74][75][76]. Similar strategies might be useful for the treatment of S. maltophilia infection.…”
Section: Treatment Considerationsmentioning
confidence: 99%